Predicting parkinson's disease using gait analysis - Fwu, Joey Hui Ning (2014)
Parkinson’s Disease (PD) is characterised by the progressive degeneration of dopamine producing cells in the pars compacta of the stantia nigra. Dopamine is a neurotransmitter that allows communication between the substantia nigra and corpus striatum, the part of the brain which coordinates proper muscle movement. Decline in dopaminergic neurons results in a fall of dopamine concentration which in turn causes the communication between substantia nigra and corpus striatum to be hindered. This causes PD patients to lose some control of their body muscle, and gives rise to early stage symptoms like involuntary shaking, rigidity, postural instability and vast decrease in speed of motion. The continuous loss of these dopamine producing neurons will cause these symptoms to become worse. Unfortunately, there is still no known cure for PD. However, medication can be used to control patient’s symptoms. Therefore, accurate and early diagnosis is of outmost importance. To date, there is also no specific medical test that can be used to diagnose PD definitely. Approximately 10 million people are estimated to be living with PD worldwide, with no discrimination of race and culture, and only 6.3 million has been diagnosed. Hence, there is a need for us to develop methods that can help diagnose PD accurately to allow patients to seek treatment early.